2006
DOI: 10.1016/j.molcel.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of AKAP Specificity for PKA Regulatory Subunits

Abstract: Localization of cyclic AMP (cAMP)-dependent protein kinase (PKA) by A kinase-anchoring proteins (AKAPs) restricts the action of this broad specificity kinase. The high-resolution crystal structures of the docking and dimerization (D/D) domain of the RIIalpha regulatory subunit of PKA both in the apo state and in complex with the high-affinity anchoring peptide AKAP-IS explain the molecular basis for AKAP-regulatory subunit recognition. AKAP-IS folds into an amphipathic alpha helix that engages an essentially p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
306
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(315 citation statements)
references
References 47 publications
9
306
0
Order By: Relevance
“…In addition, the Dpy-30 domain of Sdc1, which is a domain that was initially found in DPY-30 proteins required for sex determination and dosage compensation in Caenorhabditis elegans, has also been predicted to be a protein-protein interaction domain (39,40). Dpy-30 domains are similar to RIIa domains found in cAMP protein kinase A regulatory subunits that are known to dimerize (41)(42)(43). Therefore, the Dpy-30 domain of Sdc1 could be facilitating dimerization or interactions with Bre2.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the Dpy-30 domain of Sdc1, which is a domain that was initially found in DPY-30 proteins required for sex determination and dosage compensation in Caenorhabditis elegans, has also been predicted to be a protein-protein interaction domain (39,40). Dpy-30 domains are similar to RIIa domains found in cAMP protein kinase A regulatory subunits that are known to dimerize (41)(42)(43). Therefore, the Dpy-30 domain of Sdc1 could be facilitating dimerization or interactions with Bre2.…”
Section: Resultsmentioning
confidence: 98%
“…To date 47 human AKAP genes have been identified that encode proteins which direct PKA to defined intracellular locations (22,23). The majority of these sequester type II PKA subtypes (24)(25)(26), although several dual-function AKAPs can bind either RI or RII (27)(28)(29). Here we report that sphingosine kinase interacting protein (SKIP) anchors the type I PKA holoenzyme exclusively.…”
mentioning
confidence: 94%
“…They are the Qua1 domain from STAR proteins (43,44), the protein kinase A (PKA) type I␣ and type II␣ regulatory subunits (45,46), and the Siah-interacting protein (SIP) (47). Of these structures, Get5-C has the shortest sequence and the highest ratio of buried to exposed surface area (30% versus 28% for the next most, the crystal structure of the PKA type II␣ regulatory subunit) (48). It is significantly more thermostable than the only other dimer where this was measured, the Qua1 domain, with a T m of 74°C compared with 63°C (43).…”
Section: Discussionmentioning
confidence: 99%